STUDI AWAL TENTANG SIKAP ILMIAH MAHASISWA CALON GURU BIOLOGI DI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS SRIWIJAYA - Adeng Slamet; Fransisca Sudargo Tapilouw; Ijang Rohman (Universitas Sebelas Maret, 2014)
Preliminary studies have been conducted to obtain an overview of the scientific attitude profiles biology student teachers in the Department of Biology Education Program Mathematics Education FKIP Unsri . Data obtained by involving 65 students who attended the lectures of animal physiology . Instrument in the form of a questionnaire which contains eight characteristics include the scientific attitude of curiosity, rationality, willingness to suspend judgment, open-minded, critical thinking, objectivity, intellectual honesty, and humility. Descriptive statistics were used in the processing of the data obtained . It can be concluded that the scientific attitude of students showed a fairly good degree of attitude. Keywords : scientific attitude, prospective biology student teachers